Dissection of TAF1 neuronal splicing and implications for neurodegeneration in X-linked dystonia-parkinsonism. Issue 4 (27th October 2021) - Capponi, Simona; Stöffler, Nadja; Penney, Ellen B; Grütz, Karen; Nizamuddin, Sheikh; Vermunt, Marit W; Castelijns, Bas; Fernandez-Cerado, Cara; Legarda, G Paul; Velasco-Andrada, M Salvie; Muñoz, Edwin L; Ang, Mark A; et al.
Abstract: X-linked dystonia-parkinsonism (XDP) is a monogenic neurodegenerative disorder of the basal ganglia, which presents as a combination of hyperkinetic movements and parkinsonian features. The underlying genetic mechanism involves the insertion of a SINE-VNTR-Alu retrotransposon within the TAF1 gene. Interestingly, alterations of TAF1 have been involved in multiple neurological diseases. In XDP, the SINE-VNTR-Alu insertion in TAF1 has been proposed to result in alternative splicing defects, including the decreased incorporation of a neuron-specific microexon annotated as 34′. This mechanism has become controversial as recent studies failed to provide support. In order to resolve this conundrum, we examined the alternative splicing patterns of TAF1 mRNAs in XDP and control brains. The impact of the disease-associated SINE-VNTR-Alu on alternative splicing of microexon 34′ was further investigated in cellular assays. Subsequently, microexon 34′ incorporation was explored by RT-PCR and Nanopore long-read sequencing of TAF1 mRNAs from XDP and control brains tissues. Using cell-based splicing assays, we demonstrate that presence of the disease-associated SINE-VNTR-Alu does not affect the inclusion of microexon 34′. In addition, we show that (1) microexon 34′-containing TAF1 mRNAs are detected at similar levels in XDP as in controls and that (2) the architecture of TAF1 transcripts is remarkably similar between XDP and controls brains. These results indicate that microexon 34′ incorporation into TAF1 mRNA is not affected in XDP brains. Our findings shift the current paradigm of XDP by discounting alternative splicing of TAF1 microexon 34′ as the molecular basis for this disease. Abstract : Capponi et al. 19 propose a paradigm shift for the pathogenesis of XDP by demonstrating that microexon 34′ is incorporated within TAF1 mRNA in XDP brain specimens. Graphical Abstract: